Serum Vitamin D Status in Children with Pancreatitis (Medicine Today, 2026)
Introduction and Objective: The incidence of pancreatitis in children has significantly increased in the past two decades. Fat-soluble vitamin deficiencies (A, D, E, K) can be seen in pancreatitis. This study evaluate serum vitamin D status in children with Pancreatitis. Methods: This cross sectional analytical study was conducted at the Department of Pediatric Gastroenterology and Nutrition, BMU, Dhaka, from January, 2022 to December, 2022. A total of 30 children with the diagnosis of Pancreatitis was included as cases (Group I) and 20 children with the diagnosis of functional constipation was included as control (Group II) in the study. Serum 25-hydroxyvitamin D levels